The contemporary strain rate field in Uruguay and surrounding region – vertical velocities. (January 2021) - Baxter, Peter
Abstract: This study supplements analyses of the horizontal strain rate fields in the region in and around Uruguay presented in Baxter and Smith (2020) . Whilst the original study did not consider the vertical component, because of high levels of noise and discontinuities in the raw data, these effects have been minimized and appropriate analyses are presented with consideration of the uncertainties. The results show that, similarly to the horizontal strain rate field, the vertical velocity field in the region appears to have been influenced by two subduction earthquakes that occurred in Chile. The patterns of uplift and subsidence revealed by these analyses suggest influences from the underlying structure of the Rio de la Plata estuary, and perhaps the Mesopotamian region in Argentina, that may relate to enhanced seismicity in these specific areas. Highlights: Vertical velocities for Rio de la Plata area pre-Maule, post-Maule and post-Illapel. Pre-Maule uplift average 0.9 mm/yr changed to mixture of uplift and subsidence. Uneven distribution of changes may influence local seismicity locations. Nazca subduction events may influence timing of local earthquakes.